Ballad of Narayama [videorecording (DVD)] = Narayamabushi kō - Kinoshita, Keisuke, 1912-1998; Kinoshita, Keisuke, 1912-1998; Tanaka, Kinuyo, 1909-1977; Takahashi, Teiji, 1926-1959; Mochizuki, Yuko, 1917-1977; Ichikawa, Ennosuke, 1939-; Miyaguchi, Seiji, 1913-1985; Fukasawa, Shichirō, 1914-1987 (Criterion collection, 2013)
This haunting, kabuki-inflected version of a Japanese folk legend is set in a remote mountain village, where food is scarce and tradition dictates that citizens who have reached their seventieth year must be carried to the summit of Mount Narayama and left there to die. The sacrificial elder at the center of the tale is Orin, a dignified and dutiful woman who spends her dwindling days securing the happiness of her loyal widowed son with a respectable new wife. Includes bonus features.